Effects of three-dimensional radar display on emotion and stress during continuous climb and descent in ATC operations - Edward, Mak (2018)
The world of aviation has come a long way from its humble beginnings of just satisfying human desire to fly to a massive network of intercontinental passenger flights. This will never be achieve without the advancement of technology both in flight but also in Air Traffic Management. Only with proper procedures and vision of the air traffic situation in the sky, will aviation continue to be a safe and efficient mode of transportation. However, even with the advancement of technology, there has not be a significant improvement or change in the way information is displayed to the Air Traffic Control Of-ficers. With more complex operations and higher traffic density in the same limited airspace, conventional 2-Dimensional radar display might be overloaded with information or the lack of certain more relevant data. This will cause an increase in avoidable stress and workload to the controllers, which may impair their judgement and response time thus resulting in dire consequences. The novelty of implementing a complementary 3-Dimensional Display to aid in vertical visual representation of information is proposed. It is in hope that the additional visual aid would assist in reducing cognitive workload and stress experienced by controllers while performing complex flight operations at high traffic density condition. By observing the effects on stress and emotion experienced by the controllers, the effectiveness and feasibility of such display will be tested.